Development of a Virtual Laboratory Media Based on Green Chemistry for High School Students - Rahayu, Fatika Fani; Louise, Isana Supiah Yosephine (Journal of The Indonesian Society of Integrated Chemistry, 2026)
This study aimed to develop and evaluate a green chemistry–based virtual laboratory for chemical equilibrium topics to enhance senior high school students’ analytical thinking skills and environmental awareness. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). The development stages included expert validation, usability testing by teachers, readability testing by students, and an effectiveness test using a one-group pretest–posttest design. The participants consisted of 67 eleventh-grade students. Data on analytical thinking skills and environmental awareness were analyzed using paired sample t-tests, complemented by effect size (Cohen’s d) and normalized gain (N-gain) analyses to determine the magnitude of the learning effect. The results indicated that the green chemistry–based virtual laboratory achieved a very good level of feasibility based on evaluations by experts, teachers, and students. The effectiveness test showed a significant improvement in students’ analytical thinking skills, with the mean score increasing from 49.93 to 85.03 (p < 0.001), accompanied by a large effect size and a high N-gain category. In contrast, environmental awareness showed a slight increase in mean scores but did not reach statistical significance (p = 0.494). These findings suggest that the green chemistry–based virtual laboratory is effective in enhancing students’ analytical thinking skills. However, additional and more sustainable instructional strategies are required to achieve a significant improvement in students’ environmental awareness